Influence of Food Preservation Technology, Sanitary Hygiene, and Shelf Life on the Quality of Processed Food Products in the Indonesian Food Industry - Rissa Megavitry; Swasono, Muh. Aniar Hari; Priyana, Yana (West Science Interdisciplinary Studies, 2024)
This research investigates the intricate relationships between food preservation technology, sanitary hygiene practices, shelf life, and the quality of processed food products within the Indonesian food industry. Employing Structural Equation Modeling using Partial Least Squares (SEM-PLS), the study explores the impact of these factors on processed food quality. The sample comprises 250 participants, and the data are analyzed through various fit indices, measurement model assessments, and structural model analyses. The findings reveal significant positive relationships between food preservation technology, sanitary hygiene, shelf life, and the quality of processed food products. The results contribute valuable insights for manufacturers, regulators, and consumers, emphasizing the importance of a comprehensive approach to ensure optimal quality and safety in the processed food industry.